Intensitas Curah Hujan Memicu Tanah Longsor Dangkal di Desa Wonodadi Kulon - Gede Satya; Aris Heri Andriawan; Ahmad Ridho'i; Harjo Seputro (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract.Â Almost every year during the rainy season, landslides continue to haunt the villagers Wonodadi Kulon Ngadirojo Pacitan. Biggest landslides occurred in the past 2009 years. At least, dozens of houses were severely damaged, at least 13 cows are victims and impaired access road connecting the village to the other. Within four (4) years after the great disaster, there has been no attempt to anticipate or prevent the occurrence of landslides. Wonodadi Kulon village at an altitude of 80-500 meters above sea level to be exact in South Kendeng Mountains about 55 miles from downtown Pacitan. Its area is hilly with a slope of 68 degrees. From the survey conducted disaster seems to be increasingly threatened due to changes in land use that was originally in the form of community forest turned into farmland. Land use as agricultural land utilize a relatively steep slope, so that erosion will often occur in the form of erosion gully and soil mass movement (landslides). Erosion at this next level causing a big impact for environmental damage, such as flash floods. Public knowledge about forest conservation and water resources is still low proven that many people who are looking for firewood in the forest. Data from the local village administration mentioned critical land area of 102 hectares land area of 309.30 ha mild erosion; a land area of 410.53 ha of erosion was severe erosion and a land area of 10 ha.Keywords: disaster, landslide